2020
DOI: 10.1038/s41598-020-65879-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of concentration and phase structure of colloidal suspensions in a two-ends-open tube during drying process

Abstract: We investigated the evolution of concentration and phase structure of colloidal suspensions in a twoends-open tube during drying process. the volume fraction and crystal structure of suspension in the capillary tube were determined by reflection spectrometer during drying process. Our experimental results show: (a) evaporation takes place in two directions of the tube, though much stronger in one direction than the other; (b) during drying process, colloidal suspension column along the tube can be divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 34 publications
(18 reference statements)
1
21
0
1
Order By: Relevance
“…It was also observed that agglomeration progressed inhomogeneously in the thickness direction. A similar inhomogeneity was observed in a drying process in a capillary tube 22) and was predicted through simulations on drying suspensions. 23) However, those cases are different from drying in the production process of actual ceramics.…”
supporting
confidence: 80%
“…It was also observed that agglomeration progressed inhomogeneously in the thickness direction. A similar inhomogeneity was observed in a drying process in a capillary tube 22) and was predicted through simulations on drying suspensions. 23) However, those cases are different from drying in the production process of actual ceramics.…”
supporting
confidence: 80%
“…It can be also noticed that the consideration of tubes or channels with two open ends is classical in the studies of drying of colloidal suspensions. 14,21,22 Here we show that the classical description of unidirectional drying in capillaries used as model pores depends on the closing condition of the capillary. While drying in cylindrical capillaries closed by a solid plug follows a classical diffusiondriven behavior, a faster capillary-drying regime, characterized by a constant-rate period, 23,24 can be induced when the capillary end is in contact with a liquid plug.…”
Section: ■ Introductionmentioning
confidence: 75%
“…Stefan in 1871 was the first to describe the diffusion-driven drying in a vertical capillary tube: he showed that the evaporation of a liquid in a circular tube slows down as the air–liquid interface is receding inside the tube . Since then, round capillaries have been used in several studies to understand the flow and transport processes with different fluids such as ionic solutions , or colloidal suspensions . Unidirectional drying in capillaries has also been extensively studied by changing different parameters including geometry and wettability properties of capillaries. Generally, capillaries of polygonal cross section are considered to be closer to the geometry of real pores due to the presence of corners and angles where thick capillary films can form and strongly influence the drying kinetics ,, or imbibition process .…”
Section: Introductionmentioning
confidence: 99%
“…定为 L = 0 mm, 测量范围为 L = 0.5-15.5 mm). 反射光谱反射峰波长的变化可以 转变为粒子体积分数 𝛷 和数密度 n 的变化 [17,18] 纯水 + 滤膜 3.06×10 -6 1.49×10 -7 3.59×10 -7 3.21×10 -5 2.04×10 -6 1.12×10 -6…”
unclassified